Studi Provenance Endapan Pasir Sungai Budong-budong, Kabupaten Mamuju, Provinsi Sulawesi Barat - Herni Suryani; Ratna Husain (Universitas Tamansiswa Padang, 2022)
The reseach area administratively located in Budong-budong District, Mamuju Regency, West Sulawesi Province. The purpose of this study is to determine the provenance of sand sediments at Budong-budong River based on petrographic analysis of QFL (quartz, feldspar and rock fragments) components. There are seven representative samples namely HRN/BD-01, HRN/BD-02, HRN/BD-03, HRN/BD-04, HRN/BD-05, HRN/BD-06, HRN/BD-07 that will be observed by its optical properties. Based on genetic classification (Krynine, 1963, in Folk, 1980) and empirical classification (Folk, 1980) of quartz mineral grains, there are three types of quartz that can be identified; 1). Monocrystalline quartz with a sub-equant to elongated shape, dark straight to oblique waves (originally from granite and gneiss); 2). Composite polycrystalline quartz with sub-equant to elongated shape, straight dark to slanted wavy, straight and crenulated boundaries between crystals (derived from recrystallized metamorphic rocks); 3) Composite polycrystalline quartz with elongated shape, strongly wavy darkening, and straight/smooth, crenulated, and granulated inter-crystal boundaries (derived from depressed metamorphic rocks). The source rock of the reseach area based on point-counting result of quartz, feldspar and rock fragments on the Dickinson & Suczek (1979) QFL triangle diagram was interpreted as a recycled orogen type.